2020
DOI: 10.1016/j.vhri.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease–Specific Scores and Health Utility of Continuous Ambulatory Peritoneal Dialysis and Automated Peritoneal Dialysis Patients and Their Caregivers

Abstract: This study aimed to compare the EuroQol 5-dimension 5-level questionnaire (EQ-5D-5L), the visual analogue scale (VAS), and the Kidney Disease Quality of Life 36-Item Short-Form Survey (KDQOL-36) scores of Thai continuous ambulatory peritoneal dialysis (CAPD) and automated peritoneal dialysis (APD) patients and to compare the utility scores with the EQ-5D-5L and VAS scores of caregivers.Methods: This was a cross-sectional study completed between April 2016 and May 2017. In total, 34 CAPD patients, 30 APD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…When compared with foreign reports that used the EQ-5D-5L, a higher percentage of respondents reported the most problems with the pain/discomfort dimension, which was similar to the results of our study [18,19]. This suggests that in dialysis patients, pain/discomfort, which is the most subjective dimension related to dialysis, may still be a significant problem.…”
Section: Discussionsupporting
confidence: 87%
“…When compared with foreign reports that used the EQ-5D-5L, a higher percentage of respondents reported the most problems with the pain/discomfort dimension, which was similar to the results of our study [18,19]. This suggests that in dialysis patients, pain/discomfort, which is the most subjective dimension related to dialysis, may still be a significant problem.…”
Section: Discussionsupporting
confidence: 87%
“…When compared with foreign reports that used the EQ-5D-5L, a higher percentage of respondents reported the most problems with the pain/discomfort dimension, which was similar to the results of our study. 18,19 This suggests that in dialysis patients, pain/discomfort, which is the most subjective dimension related to dialysis, may still be a signi cant problem. In a survey of symptoms experienced by dialysis patients, Abdel-Kader et al 20 reported that tiredness or lack of energy, worry, dry skin, itchiness, trouble staying asleep, trouble falling asleep, sadness, irritability, di culty with sexual arousal, bone or joint pain, muscle cramps, and anxiousness, etc.…”
Section: Discussionmentioning
confidence: 99%